A supramolecular nanoprodrug based on a boronate ester linked curcumin complexing with water-soluble pillar[5]arene for synergistic chemotherapies. Issue 62 (8th July 2020) - Chao, Shuang; Lv, Xiukai; Ma, Ning; Shen, Ziyan; Zhang, Feiyu; Pei, Yuxin; Pei, Zhichao
Abstract : A supramolecular nanoprodrug based on the host–guest complexation of water-soluble pillar[5]arene and a boronate ester linked curcumin was constructed, which could selectively release drug in hepatoma cells by dual-responsiveness of pH and GSH. Abstract : A supramolecular nanoprodrug based on the host–guest complexation of water-soluble pillar[5]arene (WP5) and a boronate ester linked curcumin (Cur) was constructed, which had dual-responsiveness towards pH and GSH, allowing the drug to be selectively released in hepatoma cells. In vitro studies revealed that the Dox-loaded WP5G–Cur nanoprodrug achieved co-delivery of Dox/Cur. The anti-cancer efficiency could be enhanced through synergistic chemotherapies of Dox/Cur.